2020
DOI: 10.1177/1471301220927230
|View full text |Cite
|
Sign up to set email alerts
|

Community participation in activities and places among older adults with and without dementia

Abstract: Availability of community-based destinations and amenities can facilitate healthy aging by supporting older adults’ functional abilities and enabling their participation in society, especially for those experiencing declining cognitive abilities. This study used a survey tool called participation in ACTivities and places OUTside the Home for older adults, specifically designed to examine the out-of-home participation of older adults living with or without dementia, to collect data on specific places and activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
(82 reference statements)
1
18
0
2
Order By: Relevance
“…The strategies included: (a) appropriate interview setting to ensure confidentiality and comfort, like the home; (b) taking time to build rapport with the person; (c) adapting the pace of the interview; (d) rephrasing the questions if needed; (5) paying attention to lapse in concentration and possible distractions, difficulty in finding words, and possible anxiety; and (6) listening attentively and being empathic ( Cridland et al, 2016 ). It has been shown that persons living with dementia are able to share their perspectives on their own participation outside home ( Alzheimer Europe, 2011 ; Chaudhury et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategies included: (a) appropriate interview setting to ensure confidentiality and comfort, like the home; (b) taking time to build rapport with the person; (c) adapting the pace of the interview; (d) rephrasing the questions if needed; (5) paying attention to lapse in concentration and possible distractions, difficulty in finding words, and possible anxiety; and (6) listening attentively and being empathic ( Cridland et al, 2016 ). It has been shown that persons living with dementia are able to share their perspectives on their own participation outside home ( Alzheimer Europe, 2011 ; Chaudhury et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although not all spaces become places for all individuals, it supports a subjective perspective on participation ( Brown et al, 2004 ). As persons living with dementia engage in occupations in diverse places, they might create experiences of performance and perceive their participation outside home ( Chaudhury et al, 2020 ) that they are then able to tell about. Places hold individual meanings, embracing social, cultural, and political aspects, as well as spatial and temporal dimensions ( Hand et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information from parts two and three of ACT-OUT, which enquire about the activities and circumstances surrounding two places in each domain and self-perceptions of risk, as well as information from part one about places visited in the past and in relation to future were not intended for use in this study. Earlier research provides information about the development of ACT-OUT and use of the instrument in samples of older people with dementia [5,24,25], psychometric testing is ongoing in studies in different populations. With the changes mentioned above and the promising results of the testing, the ACT-OUT was judged to be suitable for assess out-of-home participation also in people in working age with cognitive impairment.…”
Section: Instrumentsmentioning
confidence: 99%
“…The term 'shrinking world' was introduced to describe the impact of dementia on people's outdoor lives (Duggan et al, 2008). Subsequently, a cross-sectional study found that over time, all community destinations and amenities outside home were more likely to be abandoned among people with dementia (Chaudhury et al, 2020). However, the same study found that participating older adults without cognitive impairment abandoned places for physical and recreational occupations.…”
Section: Occupational Science;mentioning
confidence: 99%